MOTOR ABILITY PROFILE OF JUNIOR AND SENIOR MALE SOUTH AFRICAN TAEKWONDO ATHLETES - Musa Lewis Mathunjwa; Sam Mugandani; Abidemi Kappo; Svetoslav Ivanov; Trayana Djarova-Daniels (Scientific Publishing House. NSA Press, 2017)
Introduction: The purpose of this study was to assess and compare motor abilities in young and adult male South African Taekwondo athletes. To date, knowledge of the motor ability demands of this combat sport is in its infancy. Methodology: Participants were profiled as junior (n = 25, 15.5 ± 2.6 years, 163.0 ± 13.4 cm, 53.3 ± 10.7kg) and senior (n = 20, 23.5±2.5 years, 166.8 ± 7.9cm, 68.6±7.9kg) males from a local Taekwondo (WTF) club in South Africa. Flexibility (sit-and reach), abdominal strength and endurance (60-second sit-ups and 2 minutes push-ups), explosive leg power (vertical jump), agility (T-test), aerobic power (20 m bleep test) converted to maximum oxygen uptake (VO2max) were measured. Data were analyzed with t-test for independent samples and Z-score individual radar plot statistics for each athlete. Results: There was no significant difference in agility between juniors (10.9 ±0.4s) and seniors (12.6 ± 1.2s) (p>0.05). The seniors showed significant (p<0.05) higher values in sit ups (53.1 ± 6.1 vs 48.9 ±13.8), push-ups (76.6 ± 17.1 vs 25.6 ±10.6), sit & reach (54.6 ±5.8 vs 40.1± 7.5 repetitions), horizontal jump (2.6 ± 1.1 vs 1.9 ±0.3), and VO2max (52.5 ± 2.8 vs 42.2 ±6.6) than in juniors. More extensive research is required before extending existing knowledge from this study in order to permit specialized conditioning with junior athletes leading to improved motor ability at an early stage of Taekwondo training, resulting into better combat performances. Conclusions: The results showed that the performance of senior male Taekwondo athletes is higher than the juniors'.